Molecular Mechanisms of Cardiac Remodeling and Regeneration in Physical Exercise - Dominik Schüttler; Sebastian Clauss; Ludwig T. Weckbach; Stefan Brunner (Cells, 2019)
Regular physical activity with aerobic and muscle-strengthening training protects against the occurrence and progression of cardiovascular disease and can improve cardiac function in heart failure patients. In the past decade significant advances have been made in identifying mechanisms of cardiomyocyte re-programming and renewal including an enhanced exercise-induced proliferational capacity of cardiomyocytes and its progenitor cells. Various intracellular mechanisms mediating these positive effects on cardiac function have been found in animal models of exercise and will be highlighted in this review. 1) activation of extracellular and intracellular signaling pathways including phosphatidylinositol 3 phosphate kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR), EGFR/JNK/SP-1, nitric oxide (NO)-signaling, and extracellular vesicles; 2) gene expression modulation via microRNAs (miR), in particular via miR-17-3p and miR-222; and 3) modulation of cardiac cellular metabolism and mitochondrial adaption. Understanding the cellular mechanisms, which generate an exercise-induced cardioprotective cellular phenotype with physiological hypertrophy and enhanced proliferational capacity may give rise to novel therapeutic targets. These may open up innovative strategies to preserve cardiac function after myocardial injury as well as in aged cardiac tissue.